Three-dimensional modeling of flow and deformation in idealized mild and moderate arterial vessels. Issue 13 (2nd October 2016) - Gu, Xi; Yeoh, Guan Heng; Timchenko, Victoria
Abstract: Three-dimensional numerical calculations of mild and moderate stenosed blood vessels have been performed. Large eddy simulation through a dynamic subgrid scale Smagorinsky model is applied to model the transitional and turbulent pulsatile flow. For the compliant stenosed model, fluid-structure interaction is realized through a two-way coupling between the fluid flow and the deforming vessel through the change in the external diameter due to the increment of circumferential pressure via a novel moving boundary approach. Model predictions compare very well against measured and numerical data for the centerline velocities, thickness of the flow separation zones and radial wall displacements.